The air quality characterization of Singapore bus interchanges - Tan, Jeremy Zhi Ying (2019)
Pollutants exhausted from diesel bus, including particulate matters, volatile organic compounds (VOCs) and carcinogenic polycyclic aromatic hydrocarbons (PAHs), are commonly reported in bus interchanges. Millions of commuters have to spend time waiting for their bus in the bus interchange in Singapore. Environmental exposure and associated risk during this time are of great public concern. However, limited studies have focused on the air quality in the bus interchange in Singapore. In this study, 11 representative volatile organic compounds (VOCs), 16 EPA priority pollutant PAHs were chosen to be analyzed in the indoor and bus park air samples collected from 9 air conditioned bus interchanges in Singapore. The median of total VOCs, gaseous PAHs (gPAH) and particulate-bound PAHs (pPAH) in indoor air was 49.2 µg m-3, 21.5 ng m-3 and 2.35 ng m-3 respectively. Toluene was the dominant VOC contributors for both indoor and bus park environments with 46.9% and 42.9% of the total VOCs respectively. For gPAHs, chrysene and benz[a]anthracene was found to have the highest median concentration of 4.81 ngm-3 and 1.20 ng m-3 in the indoor and bus park respectively. Chrysene and benz[a]anthracene was the dominant gPAHs contributors for indoor and bus park with 20.2% and 26.1% of the total gPAHs. As for pPAHs, benz[a]anthracene was dominant PAH in both indoor and bus park environments with median concentration of 0.30 ng m-3 and 0.71 ng m-3 respectively. Benz[a]anthracene was the most dominant PM10 pPAHs contributors for both indoor and bus park environments with 70.2% and 21.3% of the total pPAHs. The concentration level of indoor VOCs compounds was found to be significantly higher than that in bus park with an average Indoor/Bus park (I/B) ratio of 1.25, suggesting that VOCs compounds are emitted from an indoor source. The concentration level of indoor gPAHs compounds was found to be slightly higher than the concentration of the bus park with an average I/B ratio of 1.04, suggesting that gPAHs compounds are either emitted from indoor or outdoor source. The concentration of bus park pPAHs is higher than indoor concentration with an average I/B ratio of 0.71, suggesting that pPAHs is highly likely to be emitted from the bus park. Monte Carlo simulation was used to estimate exposure uncertainty and variability for the risk assessment. Overall, the concentrations of VOC were below the healthy reference values from either EPA Integrated Risk Information System (IRIS) or Singapore guideline. However, Ethylbenzene and Styrene were at levels that could exceed the stringent standards such as Office of Environmental Health Hazard Assessment (OEHHA) cancer and reproductive health-based benchmarks.